Project OPT A Study of Oral Proficiency Testing in College-Level Foreign Language Courses. Final Report - Wing, Barbara H.; Mayewski, Sandi F.; New Hampshire Univ., Durham ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
A federally funded project was undertaken at the University of New Hampshire to: (1) determine the feasibility of incorporating specific techniques of oral proficiency evaluation in college-level foreign language courses, (2) create a network of foreign language professors in northern New England colleges and universities trained in the use of oral proficiency evaluation procedures, and (3) develop a handbook of oral proficiency evaluation techniques for college-level foreign language faculty. The utility and effectiveness of the American Council on the Teaching of Foreign Languages/Educational Testing Service Oral Proficiency Interview in this context were also examined. Use of this instrument was found to be feasible at the college level, providing the benefits of more objective evaluation of oral skills, potential for increased student motivation, and a positive impact on curriculum, materials, and instructional techniques development. It is suggested that the process may be even more useful at the department level. Answers to questions often asked by faculty about the procedures and results of oral proficiency testing were provided, and additional questions emerged for further investigation. (MSE)
Sponsoring Agency: Office of International Education (ED), Washington, DC.
Contract Number: G008201400.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Second Language Programs; Examiners; Higher Education; Intercollegiate Cooperation; Interviews; Language Proficiency; Language Tests; Second Language Instruction; Speech Communication; Teacher Workshops; Test Use; Oral Proficiency Testing; ACTFL ETS Oral Proficiency Guidelines; Reports, Research; Tests/Questionnaires.